Relation of cigarette smoking and alcohol drinking in midlife with risk of cognitive impairment in late life: the Singapore Chinese Health Study. (2nd October 2018) - Wu, Jing; Dong, Wenhong; Pan, Xiong-Fei; Feng, Lei; Yuan, Jian-Min; Pan, An; Koh, Woon-Puay
Abstract: Background: the relations of cigarette smoking and alcohol drinking with risk of cognitive impairment remain inconsistent. Methods: to examine the independent and joint relations of smoking and alcohol drinking with cognitive impairment, we used data from 16, 948 men and women, who had been followed-up for 16–23 (mean of 20) years as participants of the Singapore Chinese Health Study, a population-based prospective cohort. Data on smoking and alcohol drinking were collected at baseline (1993–98), when participants were aged 45–74 (mean 53) years. Cognition was assessed using a 30-item Mini-Mental State Examination during follow-up three visits (2014–16), when participants were aged 61–96 (mean 73) years. Multivariable logistic regression models were used to estimate the odd ratios (ORs) and 95% confidence intervals (CIs). Results: cognitive impairment was present in 2, 443 (14.4%) participants. Compared with non-current smokers, current smokers had 20% increased risk (OR = 1.20, 95% CI = 1.04–1.39). Compared with those who drank less than weekly, regular alcohol drinking (at least weekly) had 17% increased risk (OR = 1.17, 95% CI = 1.01–1.36). Compared with those who were neither smokers nor drinkers, those who were either current smokers or regular drinkers alone had no significantly increased risk, while the risk was highest in those who were both current smokers and regular drinkers (OR = 1.77, 95% CI = 1.39–2.26, P interaction = 0.003). Conclusions: co-existence of smoking and regular alcohol drinking at midlife had a much stronger impact than the individual factors on risk of cognitive impairment in late life.